Sensitive LC–MS/MS methods for the quantification of RGH-188 and its active metabolites, desmethyl- and didesmethyl-RGH-188 in human plasma and urine - PASZTOR MEZAROS, Gabriella; AGAI-CSONGOR, Eva; KAPAS, Margit (Journal of pharmaceutical and biomedical analysis, 2008)
Selective and sensitive LC–MS/MS methods have been developed and validated for simultaneous determination of RGH-188, a novel atypical antipsychotic, and its two active metabolites, desmethyl- and didesmethyl-RGH-188 in human plasma and urine. Deuterated analytes, [ 2H 6]-RGH-188, [ 2H 3]-desmethyl-RGH-188 and [ 2H 8]-didesmethyl-RGH-188 were used as internal standards (IS). The compounds were isolated from the alkalized biological matrix using liquid–liquid extraction (LLE) and the extracts were analysed by reversed-phase HPLC with MS/MS detection. The chromatographic run time was 5.0 min per injection. The PE Sciex API 365 mass spectrometer was equipped with a TurboIonSpray ® interface and operated in positive-ion, multiple reaction monitoring (MRM) mode. The mass transitions monitored were m/ z 427.3 → 382.2, 413.2 → 382.2, 399.2 → 382.2, 433.3 → 382.2, 416.2 → 382.2 and 407.3 → 390.2 for RGH-188, desmethyl-RGH-188, didesmethyl-RGH-188, [ 2H 6]-RGH-188, [ 2H 3]-desmethyl-RGH-188 and [ 2H 8]-didesmethyl-RGH-188, respectively. The lower limit of quantification (LLOQ) was 0.05 and 0.1 ng/ml for RGH-188 and its metabolites, respectively, using 1 ml of plasma. LLOQ in 1 ml of urine was 0.1 ng/ml for all three analytes. The methods were validated for selectivity, linearity, accuracy and precision. The lower limit of quantification, dilution integrity, matrix effect, stability of the analytes in the biological matrix during short- and long-term storage and after three freeze–thaw cycles were also tested. The assays were simple, specific and robust enough to support clinical development of RGH-188.